The Impact of the Investment Law and the Instructions Issued Under it on the Investment Process in the Kurdistan Region: (Comparative analytical study) - Sheikho , Assistant Lecturer Mohammed A.; Raool, Assistant Lecturer Luqman H.; Dr. Hawry Kamal (Mitanni Journal of Humanitarian Sciences, 2023)
Abstract Investment is the desired goal for all countries to develop and develop their economic cycle and build the country's infrastructure. Therefore, all countries seek to encourage and attract investors at the national and international levels to carry out investment projects in various sectors in the country, by issuing laws that regulate the investment process in a way that aims to achieve the goals that The state seeks to achieve it, and at the same time guarantees the rights of the investor and gives him more confidence and reassurance.